Carbon and nutrient burial within Peruvian coastal marsh driven by anthropogenic activities. (August 2022) - Pérez, Alexander; Escobedo, Rosario; Castro, Rodrigo; Jesus, Rosa; Cardich, Jorge; Romero, Pedro E.; Salas-Gismondi, Rodolfo; Ochoa, Diana; Aponte, Héctor; Sanders, Christian J.; Carré, Matthieu
Abstract: This research assessed carbon and nutrient burial during the past ~60 years within a Peruvian coastal marsh ecosystem affected by anthropogenic activities, by examining total organic carbon (TOC), total nitrogen (TN) and isotopes (δ 13 C and δ 15 N) tracers in two dated sediment cores. Significantly higher TOC and TN burial, up to 416.4 ± 65.0 and 0.7 ± 0.1 g m −2  year −1 respectively, were observed after an uncontrolled urban expansion starting in the early 1970's to the 1990's. The TOC and TN burial rates were up to twofold higher than those observed for preserved coastal marshes. Furthermore, the decreased δ 13 C values (−16.1 ± 0.6 ‰) and increasing δ 15 N values (+10.6 ± 2.6 ‰) indicate higher deposition of algal material and urban sewage during the same period. The higher burial rates during 1970's–1990's and reduced rates thereafter evidenced the role of coastal marsh ecosystems plays in sequestering carbon and nutrients. Highlights: Carbon (TOC) and nitrogen (TN) burial in a saltmarsh was studied to determine impact. Significantly higher TOC and TN burial were observed after an urban expansion. TOC and TN burial were twofold higher than those observed for preserved saltmarsh. δ 13 C and δ 15 N values indicate higher heavy nitrogen and algal deposition.